The Essence of Telemedicine for Bridging the Gap in Health Services - Wiweko, Budi; Zakirah, Sarah Chairani; Luthfi, Atha (UI Scholars Hub, 2021)
This study aimed to review the essence of telemedicine in this modern era of technology and innovation, especially in developing countries. It also investigated the regulation aspect as the main component for healthcare services. There were five main categories of telemedicine: revenue stream and technology literacy, health facilities, human resources, data authorization and security, and health protocol. Furthermore, when combined with wearable devices, it enhanced healthcare delivery opportunities. There were two major components of global electronic health, namely telehealth and health informatics, based one-commerce and e-learning systems. The World Health Organization (WHO) has been able to describe the roles of telehealth services in developing countries.However, some related issues were needed to be well managed, such as the patient data security. It was found that the regular training and evaluation of people with poor educational background, low income, and stress were the main reasons most communities attend healthcare services despite mild sickness.Therefore, those need to be enlightened on the roles and importance of telehealth services.